A revision of the purse-web spider genus Calommata Lucas, 1837 (Araneae, Atypidae) in the Afrotropical Region - Fourie, René (Pensoft Publishers, 2011)
Abstract. The purse-web spider genus Calommata Lucas, 1837 is revised in the Afrotropical Region. Following examination of the female type material, Calommata transvaalica Hewitt, 1916 is removed from synonymy with Calommata simoni Pocock, 1903 and revalidated. The females of both species are redescribed and their males described for the first time. While Calommata simoni is very widespread across tropical Africa, Calommata transvaalica is endemic to northern South Africa. Four new species are described, all known only from males: Calommata megae sp. n. (Zimbabwe), Calommata meridionalis sp. n. (South Africa), Calommata namibica sp. n. (Namibia) and Calommata tibialis sp. n. (Ivory Coast and Togo). Notes are presented on the biology of each species.